2001
DOI: 10.1073/pnas.201301498
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of light signaling to the suprachiasmatic nucleus in vitamin A-deficient mice

Abstract: To investigate the role of retinal-based pigments (opsins) in circadian photoreception in mice, animals mutated in plasma retinol binding protein were placed on a vitamin A-free diet and tested for photic induction of gene expression in the suprachiasmatic nucleus. After 10 months on the vitamin A-free diet, the majority of mice contained no detectable retinal in their eyes. These mice demonstrated fully intact photic signaling to the suprachiasmatic nucleus as measured by acute mPer mRNA induction in the supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 50 publications
4
54
1
Order By: Relevance
“…Either melanopsin can utilize a chromophore that does not require LRAT activity (albeit with reduced function), or another photopigment is capable of mediating PLR function in the presence of melanopsin apoprotein. Interestingly, another inner retina-mediated process, namely retinohypothalamic signaling to the suprachiasmatic nucleus, important for circadian rhythm entrainment, is preserved in the face of near total vitamin A depletion (54).…”
Section: Discussionmentioning
confidence: 99%
“…Either melanopsin can utilize a chromophore that does not require LRAT activity (albeit with reduced function), or another photopigment is capable of mediating PLR function in the presence of melanopsin apoprotein. Interestingly, another inner retina-mediated process, namely retinohypothalamic signaling to the suprachiasmatic nucleus, important for circadian rhythm entrainment, is preserved in the face of near total vitamin A depletion (54).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, one additional argument in favor of mCrys being involved in the light induction of mPer1. Retinal-depleted micewhich should be devoid of functional opsins-show normal mPer1 and mPer2 induction in the SCN, suggesting the existence of nonopsin photoreceptors in the eye (Thompson et al, 2001). Yet it is still possible that residual retinal leads to some functional opsins in these mice, which is also suggested by the normal mPer2 induction in the retinal-depleted mice.…”
Section: Brdm1mentioning
confidence: 99%
“…Although rhodopsins also contribute to Drosophila circadian photoreception (HelfrichForster et al 2001), a major circadian photoreceptor in this organism was shown to be a cryptochrome, with flavin adenin dinucleotide (FAD) and methenyltetrahydrofolate (MTHF) as chromophores Stanewsky et al 1998). Mammalian cryptochromes may also be circadian photoreceptors (Selby et al 2000;Thompson et al 2001), although the evidence is stronger that they are important central clock components (Kume et al 1999;van der Horst et al 1999). Cryptochromes are closely related to photolyases (blue light-activated DNA repair enzymes), which led to the idea that the DNA binding property of photolyases was retained in cryptochromes (Cashmore et al 1999;Emery et al 1998).…”
Section: Introductionmentioning
confidence: 99%